Impact of COVID-19 on Utilization of Healthcare Services Among People Living with HIV (PLHIV): A Systematic Review - Enyinnaya Ukaegbu; Maulenkul Tilektes; Antonio Sarria-Santamera (Medicina)
Background and Objectives: People living with HIV/AIDS have been impacted notably by the COVID-19 pandemic in diverse dimensions. Although some impacts of COVID-19 on PLHIV have been well documented, there is still insufficient research that captures the overall understanding of the implications of COVID-19 for the healthcare utilization among PLHIV. This review aims to evaluate the impact of COVID-19 on PLHIV, narrowing it down to women living with HIV/AIDS. Materials and Methods: An electronic database search of primary studies that obtained information from health facility data regarding PLHIV since 2020 was carried out according to the PRISMA statement. A combination of search terms, e.g., “COVID-19 pandemic”, “SARS-CoV-2”, “Health services utilization”, “People living with Human immunodeficiency virus”, was included. Results: There was an overall decline in the utilization of health services such as medical consultations, ART uptake, and viral load monitoring by PLHIV at primary health centers at the forefront of care delivery. However, the countries in the sub-Saharan African region showed a progressive service increase over the pandemic. There was a scarcity of research on the impact of COVID-19 on women populations living with HIV/AIDS. Other methods of healthcare delivery such as telemedicine and postage services were instrumental to the delivery of HIV care services. Conclusions: The COVID-19 pandemic reduced the overall uptake of healthcare services among PLHIV and women living with HIV/AIDS. There is a need to boost research and strengthen health emergency preparedness for PLHIV, particularly women living with HIV/AIDS, during pandemics and further harness and maximize the use of contemporary healthcare delivery methods other than the traditional ones.